The World at Risk: Vulnerability, Precarity, and Connectedness - Keenan, James F. (Theological studies, 2020)
This article considers the world at risk; in particular it focuses on the three topics covered at the international conference of Catholic Theological Ethics in the World Church in 2018 in Sarajevo: climate change, its impact on marginalized populations, and the tragic banality of contemporary political leadership. The article turns to a proposal by Trinity College's Linda Hogan to develop an ethics of vulnerability so as to respond to the triple crisis. After examining contemporary writings on both vulnerability and precarity by Judith Butler and others, it concludes by applying the ethics of vulnerability to other urgent cases as well.